If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 + -1(x + 2x + -2) = 0 Reorder the terms: 60 + -1(-2 + x + 2x) = 0 Combine like terms: x + 2x = 3x 60 + -1(-2 + 3x) = 0 60 + (-2 * -1 + 3x * -1) = 0 60 + (2 + -3x) = 0 Combine like terms: 60 + 2 = 62 62 + -3x = 0 Solving 62 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-62' to each side of the equation. 62 + -62 + -3x = 0 + -62 Combine like terms: 62 + -62 = 0 0 + -3x = 0 + -62 -3x = 0 + -62 Combine like terms: 0 + -62 = -62 -3x = -62 Divide each side by '-3'. x = 20.66666667 Simplifying x = 20.66666667
| 5x-2=22+3x | | 6-9+66=30 | | 3(x-2)(x-2)=27 | | 6p+6=2+2p | | 6v+21=-3(3-7v) | | 5x-2=5(x-1) | | (9x+6)+(3x)=90 | | 12x+1000= | | 5p-2-3p=16 | | 12x^2+4x+4=0 | | 3x+60-2=0 | | -6(x+8)-45=2-53 | | 19-12=x/8 | | 14=x+(x*.08) | | 4x-15+2x+3=48 | | -4x-15=19 | | 2(x-8)=8x+20 | | -5n=13-3 | | 5x-2=-8x+24 | | -16+3n=4n+7n | | 5x+6=2x+36 | | 4z+8x=360 | | 5x+6=2x+37 | | n-3+7=10+7n | | 10x-12+10x+32=180 | | -12x=15 | | 5k+5=-2-3k+k | | 7z=13-34 | | 5-2(x+3)=7 | | 9=72-13Z+2+M | | -3*2k= | | 2w+8=37 |